(untitled) - Monaghan, Annabel (New York, 2023)
"The ultimate summer nostalgia read about an engaged woman who comes face to face with her first love who she hasn't seen in fourteen years, but who she spent every summer with from age five to seventeen when he broke her heart, calling into question everything she thought she knew about their love story, and herself"--
Keywords: Fiction; Self-realization in women; Fiction; Summer; Fiction; Beaches; Fiction; Betrothal; Fiction; First loves; Fiction; Man-woman relationships; Romance fiction